2019
DOI: 10.1186/s12931-019-1130-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of exacerbations and blood eosinophils in UK and US COPD populations

Abstract: Background Blood eosinophil counts and history of exacerbations have been proposed as predictors of patients with chronic obstructive pulmonary disease (COPD) who may benefit from triple therapy (inhaled corticosteroid, long-acting β 2 -agonist and long-acting muscarinic antagonist). Methods In a retrospective cohort analysis we examined the profiles of COPD patients from the UK Clinical Practice Research Datalink (CPRD) and US Optum Clinforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…This may be due to the smaller number of patients in higher blood eosinophil group, as well as the potential effect of the two treatment arms [21,22,35]. We did not observe any association between smoking status (current and ex-smokers) and the efficacy of the two treatments on the risk of exacerbations [20,35]. Despite the evidence supporting reduced steroid responsiveness in current smokers with asthma, the efficacy of ICS in current smokers with COPD is still rather controversial.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This may be due to the smaller number of patients in higher blood eosinophil group, as well as the potential effect of the two treatment arms [21,22,35]. We did not observe any association between smoking status (current and ex-smokers) and the efficacy of the two treatments on the risk of exacerbations [20,35]. Despite the evidence supporting reduced steroid responsiveness in current smokers with asthma, the efficacy of ICS in current smokers with COPD is still rather controversial.…”
Section: Discussionmentioning
confidence: 65%
“…Unlike previous reports, our results did not show any impact of blood eosinophil on the future risks of exacerbations. This may be due to the smaller number of patients in higher blood eosinophil group, as well as the potential effect of the two treatment arms [21,22,35]. We did not observe any association between smoking status (current and ex-smokers) and the efficacy of the two treatments on the risk of exacerbations [20,35].…”
Section: Discussionmentioning
confidence: 68%
“…Significant variability in blood eosinophil levels has been shown throughout the course of COPD (38,39). To investigate the stability of blood eosinophilic inflammation (≥2%), subjects were classified into predominantly (PE), intermittently (IE), and rarely (RE) eosinophilic groups in one study (40).…”
Section: Discussionmentioning
confidence: 99%
“…What perhaps is more surprising is that eosinophilia, which is typically associated with asthma, occurs in a subset of patients with COPD. In a recent study of patient data from general practice in both the UK and USA (around 43 000 patients), eosinophilia was evident in 31% and 25% of the UK and USA cohorts of stable COPD patients, respectively [9], and some studies have reported eosinophilia in up to 40% of patients with COPD [10]. However, COPD studies from the 1990s, often with small numbers of patients, had negative outcomes when looking at the effect of corticosteroid treatment on eosinophilic inflammation [11].…”
Section: Eosinophils Corticosteroids and Copdmentioning
confidence: 99%